Synthesis of Cu2O micro/nanocrystals for catalytic combustion of high-concentration CO: The crucial role of glucose. (February 2023) - Ma, Pandong; Zhang, Chenhang; Dou, Baojuan; Yi, Xiaokun; Bin, Feng; Liang, Wenjun
Abstract: Cubic Cu2 O micro/nanocrystals were successfully synthesized by liquid-phase reduction using copper salt of CuSO4 or CuCl2 ·2H2 O, and glucose or ascorbic acid as reducing agent, respectively. The activity of the catalysts was evaluated by light-off curves of CO self-sustained catalytic combustion via temperature-programmed oxidation of CO (CO-TPO), with the results showing the activity of catalysts following the order of Cu2 O–Cl-GLU > Cu2 O– S -GLU > Cu2 O– S -AA > Cu2 O–Cl-AA, (Cl denotes CuCl2 ·2H2 O, GLU denotes glucose, S denotes CuSO4 and AA denotes ascorbic acid, respectively), corresponding to the ignition temperature of 109 °C, 122 °C, 137 °C and 186 °C, respectively. The crystal structure, elemental valence, morphology and redox property of the prepared catalysts were analyzed by using various characterization techniques. Combined with in situ infrared spectrum, the CO self-sustained catalytic combustion over Cu2 O catalysts mainly follows the Mars-van-Krevelen (M-v-K) mechanism: the adsorbed and activated CO reacts with lattice oxygen to yield CO2 and oxygen vacancy, and then the oxygen vacancy can be replenished by gaseous oxygen. Combined with catalytic performance of high-concentration CO, it is found that the catalysts prepared using glucose as reducing agent are more angular compared with ascorbic acid. The Cu2 O–Cl-GLU synthesized with glucose and CuCl2 ·2H2 O exhibits the best catalytic activity among all the catalysts tested, attributing to its more obvious edge and rough crystal surface. The unique structure of Cu2 O–Cl-GLU leads to the high exposure rate and coordination unsaturation of atoms on the cubic Cu2 O micro/nanocrystals that can improve the ability of activating gaseous O2 and low temperature reducibility, and consequently facilitating the catalytic activity. Graphical abstract: Cycle path diagram of CO oxidation reaction (a) and schematic diagram of CO oxidation reaction on Cu2 O (b). Image 1 Highlights: Effects of reducing agent on catalytic properties is greater than that of copper salt. High concentration CO can achieve self-sustained catalytic combustion on obtained Cu2 O. Glucose enhances unsaturation of Cu atoms contributing to high activity. Chemically adsorbed oxygen on Cu2 O surface promotes CO ignition.